DEVELOPMENT OF COMPETITIVE STRATEGIES OF RETAILERS IN FOOD MARKET - Oxana V. Khlopenko (Advanced Engineering Research, 2011)
Advice on the competitive strategies choice by the food retailers subject to their strategic competitive position is provided.